Enhancing E-ID cards authentication with NFC - Vale, Tariq Youssef Costa do (2023)
In contemporary times, the profound impact of Information and Communication Technologies (ICT) in daily life introduces numerous challenges for the average citizen. These challenges encompass managing digital profiles across a variety of services and institutions, from retail shops to tax obligations. The escalating demand for authentication services for even basic tasks can be daunting. In response, many countries have devised sophisticated solutions to centralize authentication services around a single Electronic Identification (E-ID) card. This card facilitates diverse tasks such as paying taxes, obtaining criminal records, interacting with financial institutions, and digitally signing electronic documents. However, the inconvenience associated with using a smartcard reader for authentication and the intricacies of Mobile Digital Tokens can be overwhelming, especially for those less familiar with digital tools. Near-field communication (NFC) is an increasingly popular technology, recognized for its simplicity and speed. This thesis proposes a secure, user-friendly, and efficient method to implement NFC-based authentication in an E-ID card. This thesis explores existing authentication methods and offers an enhanced solution. Safety remains a primary concern, and this is addressed by integrating cryptography techniques, including public key certificates and Multi-Factor Authentication (MFA), to ensure robust authentication.